Instructional Preferences of Students in Transnational Chinese and English Language MBA Programs - Bambacas, Mary; Sanderson, Gavin (Journal of University Teaching and Learning Practice, 2011)
This paper reports on Stage 1 of a learning and teaching project focused on students studying in the Chinese and English language delivery of transnational Master of Business Administration (MBA) programs of an Australian university. The programs are delivered using limited and intensive face-to-face teaching augmented by self-directed and web-based learning, and ongoing (mainly email) contact with lecturers before and after they have returned to Australia. The aim of this stage of the project is to provide a greater understanding of students’ instructional preferences so that, where appropriate, lecturers can better scaffold learning and teaching arrangements (Stage 2 of the project) to assist them to meet the learning objectives of the MBA program. Survey data was collected from students studying the MBA in Hong Kong and Singapore in English (EMBA), and in Hong Kong, Singapore and Taiwan in Chinese (CMBA). Findings demonstrate that whilst students ranked teacher directed, face-to-face instructional delivery highly, they also indicated that an independent, web-based learning environment was their least-preferred approach to learning. These findings put lecturers in a more informed position when it comes to them planning how to best assist students from Confucian-heritage backgrounds to work productively and successfully in their studies.